Young people’s recall and perceptions of gambling advertising and intentions to gamble on sport - Nyemcsok, C.; Thomas, S.; Bestman, A.; Pitt, H.; Daube, Mike; Cassidy, R. (2018)
Background: There has been an increased international policy focus on the factors that may contribute to, and prevent, the normalization of gambling for young people. However, there is still limited research, which investigates the role of advertising in shaping young people’s gambling attitudes and consumption intentions. Methods: Mixed methods study of 111 young people aged 11–16 years recruited from community basketball stadiums in Victoria, Australia, between May and July 2018. Interviewer-assisted surveys investigated recall and awareness of sports betting brands, perceptions of promotional strategies, intention to gamble, and reasons for betting on particular sports. Quantitative data were analyzed using descriptive statistics and ?2 tests. Thematic analyses were used to interpret qualitative responses. Results: Young people had high recall and awareness of advertising, with most able to name at least one betting brand (n = 90, 81.1%), and many demonstrating a high awareness of the distinct characteristics (such as colors and appeal strategies) of different brands. A fifth of young people (n = 25, 22.5%) expressed intentions to gamble at 18 years, with boys significantly more likely than girls to state they would gamble (?2 = 10.90, p = .001). Young people perceived that advertising strategies associated with inducement promotions would be the most influential in encouraging individuals to gamble. While many young people took promotions at face value, there was evidence that some were able to critically engage with and challenge the messages within marketing. Discussion and conclusions: Current regulatory structures appear to be ineffective in limiting young people’s recall and awareness of gambling advertising. Lessons from tobacco control support the application of precautionary approaches as a more effective way to limit young people’s development of positive gambling attitudes and behaviors.